2018
DOI: 10.18174/449789
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring getijdenturbines Oosterscheldekering : Jaarrapportage 2017

Abstract: Dit project is mede mogelijk gemaakt door een bijdrage uit het Europees Fonds voor Regionale Ontwikkeling in het kader van OP-Zuid en het ministerie van Economische Zaken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 5 publications
0
8
0
2
Order By: Relevance
“…The numbers of animals counted per survey may have been influenced by many factors such as the weather conditions (especially in 2010), diving behavior of the porpoises, and training of observers. The numbers observed before and after turbine installation are similar (Leopold and Scholl, 2018). Both the number of live porpoises seen and the number of dead porpoises stranded in the Eastern Scheldt seem to be stable during the monitoring period (Leopold and Scholl, 2018).…”
Section: Numbers Of Harbor Porpoises In the Eastern Scheldtmentioning
confidence: 80%
See 4 more Smart Citations
“…The numbers of animals counted per survey may have been influenced by many factors such as the weather conditions (especially in 2010), diving behavior of the porpoises, and training of observers. The numbers observed before and after turbine installation are similar (Leopold and Scholl, 2018). Both the number of live porpoises seen and the number of dead porpoises stranded in the Eastern Scheldt seem to be stable during the monitoring period (Leopold and Scholl, 2018).…”
Section: Numbers Of Harbor Porpoises In the Eastern Scheldtmentioning
confidence: 80%
“…Both the number of live porpoises seen and the number of dead porpoises stranded in the Eastern Scheldt seem to be stable during the monitoring period (Leopold and Scholl, 2018). Photo identification studies show that some individual porpoises have been observed often, which suggests that once they are in the Eastern Scheldt, they tend not to leave (Leopold and Scholl, 2018), this was also concluded from prey analysis (Jansen et al, 2013). However, it is not known whether or not harbor porpoises swim in and out of the Eastern Scheldt by crossing the barrier more than once.…”
Section: Numbers Of Harbor Porpoises In the Eastern Scheldtmentioning
confidence: 92%
See 3 more Smart Citations